1975
DOI: 10.1113/jphysiol.1975.sp011184
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and endocrine responses to feeding in the young calf.

Abstract: SUMMARY1. A number of cardiovascular and endocrine responses which occur during and after feeding in the unweaned calf are described.2. There was a substantial increase in both heart rate and mean aortic blood pressure during feeding in these animals. This occurred within the first few seconds and persisted throughout the period of ingestion.3. The concentrations of glucose, insulin and gastrin in arterial plasma rose abruptly during, or immediately after, feeding and elevated values persisted for at least 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
24
0
3

Year Published

1979
1979
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 28 publications
9
24
0
3
Order By: Relevance
“…In the study of sheep cited above, BlairWest and Brook (18) not only observed increases in HR and BP similar to those seen in other species (1,4,5,15,17), but also noted the production of copious amounts of saliva. This resulted in a reduction in renal blood flow with the consequent retention of sodium and water, and a reduction in the circulatory volume with a rise in plasma renin concentrations (18).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…In the study of sheep cited above, BlairWest and Brook (18) not only observed increases in HR and BP similar to those seen in other species (1,4,5,15,17), but also noted the production of copious amounts of saliva. This resulted in a reduction in renal blood flow with the consequent retention of sodium and water, and a reduction in the circulatory volume with a rise in plasma renin concentrations (18).…”
supporting
confidence: 64%
“…These include alterations in blood pressure (BP), heart rate (HR), and blood flow to and from those tissues and organs that participate in neural and hormonal functions (1)(2)(3)(4)(5). Sleep, for example, is an activity accompanied by a fall in BP (6).…”
mentioning
confidence: 99%
“…The central administration of OT induces the expression of the FOS protein in regions involved in the control of food intake (Olson et al 1993). Plasma osmolality also increases in response to food intake and the ingestion of sodium (Bloom et al 1975, Houpt et al 1983, Burlet et al 1992; this increase involves both inhibitory and excitatory control mechanisms (Cunningham & Sawchenko 1991).…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Or, chez le veau préruminant un pic a été détecté au cours des 10 min qui suivent l'ingestion d'un repas témoin (Bloom et al, 1975). Aucune variation de la glucagonémie n'a été induite par l'excès alimentaire de leucine chez l'agneau préruminant ( fig.…”
unclassified